PROFIL KONDISI FISIK ATLET BULUTANGKIS JUNIOR INDONESIA - kosasih, Alam Hadi; Permana, Dian; Zinat, Irfan (JUARA : Jurnal Olahraga, 2025)
The purpose of this study was to reveal the profile of the physical condition of Indonesian junior badminton athletes. Participants in this study were 40 badminton athletes (age = 14-18 years, Male = 31, Female = 9). Research instruments on physical conditions are endurance, strength & conditioning, speed, flexibility, and coordination. Data analysis with descriptive statistics. This study concludes the condition profile as follows; 1) Endurance in male athletes when viewed from an average of 60.29, then falls into the "good" category, then female athletes when viewed from an average of 54.86, then falls into the "good" category; 2) Strength & conditioning in male athletes when viewed from an average of 5.70, then it is included in the "enough" category, then female athletes if viewed from an average of 4.78, it is in the "good" category; 3) Speed for male athletes when viewed from the average of 3.30, is in the "very good" category, then for female athletes if viewed from the average of 3.71, it is in the "excellent" category; 4) Flexibility in male athletes when viewed from an average of 21.42, is in the "good" category, then female athletes when viewed from an average of 14.22, is in the "enough" category; 5) Coordination for male athletes when viewed from an average of 11.46, is included in the "good" category, then for female athletes when viewed from an average of 13.49, it is included in the "good" category. Suggestions for future research are related to the test instruments used.